Chemical chaperone-conjugated exendin-4 as a cytoprotective agent for pancreatic β-cells. (December 2018) - Son, Sohee; Park, Eun Ji; Kim, Yejin; Lee, Kang Choon; Na, Dong Hee
Graphical abstract: Highlights: Conjugation of tauroursodeoxycholic acid (TUDCA) to Lys-27 of exendin-4 (Ex4). TUDCA-Lys 27 -Ex4 (TUM1-Ex4) showed strong activity as a GLP-1 receptor agonist. TUM1-Ex4 reduced the expression of GRP78 and levels of phosphorylated eIF2α. Abstract: Endoplasmic reticulum stress has been considered a major cause of pancreatic β-cell dysfunction and apoptosis leading to diabetes. Glucagon-like peptide-1 receptor activation and chemical chaperones have been known to reduce endoplasmic reticulum stress and improve β-cell function and survival. The purpose of this study was to prepare and evaluate the chemical chaperone tauroursodeoxycholic acid-conjugated exendin-4 as a protective agent for pancreatic β-cells. Mono-tauroursodeoxycholic acid-Lys 27 -exendin-4 conjugate (TUM1-Ex4) showed better receptor binding affinity than other conjugates with strong in vitro insulinotropic activity in rat pancreatic β-cells and in vivo hypoglycemic activity in type 2 diabetic db/db mice. In INS-1 cells under endoplasmic reticulum stress induced by thapsigargin, TUM1-Ex4 promoted cell survival in a dose-dependent manner. In western blot analysis, TUM1-Ex4 reduced the expression of the endoplasmic reticulum stress marker GRP78 and phosphorylation of the translation initiation factor eIF2α. These results reveal that TUM1-Ex4 accelerates translational recovery and contributes to β-cell protection and survival. The present study indicates that the chemical chaperone-coupled glucagon-like peptide-1 receptor agonist is a feasible therapeutic strategy to enhance β-cell function and survival.